The impact of oxygen exothermicity on energy quality of biofuels and catalytic upgrading - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2020.